Stone artefacts made of amphibolite from the settlement of the Linear Band Pottery culture at the site 22 in Świlcza (Świlcza commune), in the context of the settlement network in the area of Rzeszów - Nowak, Joanna (Fundacja Rzeszowskiego Ośrodka Archeologicznego, 2014)
This article discusses stone artefacts made of amphibolite, which have been discovered within the area of the settlement of the Linear Band Pottery culture (LBK) at the site 22 in Świlcza (Świlcza commune). The researchers have found three adzes and a part of an unspecified tool at the site. These tools can be ascribed to the middle and late phase of the Linear Band Pottery culture. The products from amphibolite in the shape of a shoe-last are quite common at the sites of the discussed culture. The problem of naming this type of objects has been emphasised and a need to interpret their functions has been highlighted. The settlement in Świlcza is a part of a settlement network of that culture in the area of Rzeszow, which is also one of many settlement agglomerations of the Early Neolithic period in south-eastern Poland. Therefore, both the site itself and the artefacts recorded there will be presented in the context of the Linear Band Pottery culture settlement in the discussed area and more broadly in the light of similar finds from the area of the Czech Republic and Slovakia.
Kamienne zabytki z amfibolitu z osady kultury ceramiki wstęgowej rytej na stanowisku 22 w Świlczy (gm. Świlcza), w kontekście sieci osadniczej w rejonie Rzeszowa
Keywords: the Linear Band Pottery Culture (LBK); amphibolite tools; so-called “shoe-last” adze; polished stone pick; Early Neolithic settlement; working tools; settlement pit